LB-001 Suppressor Of Cytokine Signalling 3 (socs3) Impacts On Intestinal Epithelial Cell Proliferation During Intestinal Helminth Infection. (9th June 2014) - Shaw, E; Else, K; Rigby, R
Abstract : Introduction: In the murine model of whip worm infection Trichuris muris invades cecal and colonic epithelial cells and elicits either a Th1 (susceptible) or Th2 (resistant) immune response. An increase in intestinal epithelial cell (IEC) turnover has been implicated to aid in the physical expulsion of the worm in the resistant phenotype. 1 Failure to initiate a transient increase in IEC turnover can lead to chronic infection. SOCS3 limits IEC proliferation and its loss is associated with increased tumour growth and hyperproliferation in cancer and intestinal injury models. 2 SOCS3 may have an important role in regulating IEC in intestinal homeostasis and may mediate resistance to pathogens. This study aims to examine the role of SOCS3 in regulating IEC turnover in a murine model of T. muris infection. Methods: SOCS3 expression was examined in the intestine of T. muris resistant or susceptible mice by immunohistochemistry and real-time PCR. SOCS3 IEC (villin cre) knockdown (SOCS3 fl/fl -VC) and control (SOCS3 fl/fl -WT) mice were infected with T. muris and intestinal tissue examined at 3, 12, 21 and 35 days after infection. Crypt depth was measured and cell proliferation rates determined using an EdU Click-iT assay. Worm burden and immune response was assessed at 35 days to determine outcome of infection. Results: SOCS3 expression (mRNA and protein) was increased in the intestine of susceptible mice compared with resistant mice post T. muris infection. We hypothesised that increased SOCS3 may limit IEC turnover and therefore reduced SOCS3 expression may promote IEC proliferation and expulsion of parasites. At 35 days post-infection there was an increase in proliferation in cecal tissue from SOCS3 fl/fl -VC vs. SOCS3 fl/fl -WT mice. This supports an increase in cell turnover, as no concomitant change in crypt depth was observed. Examination of tissue from SOCS3 fl/fl -VC mice during the early stages of T. muris infection (days 3 and 12) showed little difference in crypt depth, proliferation or inflammation compared to control, suggesting that IEC SOCS3 impacts on crypt dynamics at >12 days post-infection. Evidence of T. muris infection was observed in both SOCS3 fl/fl -VC and SOCS3 fl/fl -WT mice at 35 days, but differences in worm burden and immune response remain to be determined. Conclusion: Intestinal epithelial cell SOCS3 impacts on crypt dynamics during intestinal helminth infection. SOCS3 may play a role in susceptibility to intestinal parasites. Disclosure of Interest: None Declared.